Absence of small hive beetles from flowering plants. Issue 5 (20th October 2017) - Willcox, Bryony K.; Howlett, Brad G.; Neumann, Peter
Abstract : Small hive beetles (SHBs), Aethina tumida (Coleoptera: Nitidulidae), are parasites and scavengers of honey bee colonies in their endemic range in sub-Saharan Africa as well as in their new distribution range. Even though flowering plants may in principle also serve as a food for SHBs, evidence so far suggest that this beetle is unlikely to visit flowers. However, field data remain scarce calling for more efforts to investigate the potential of flowers as reservoirs for this pest of social bees. Here, we conducted extensive field surveys of flowering plants in Australia. Despite the very large sample size, not a single adult SHB was found on any of the flowers. This is in line with an earlier field survey. Since SHBs were also absent from fruits in another surveys, it appears as if alternative food sources outside of bee colonies are of minor importance only for SHBs.